2019
DOI: 10.1186/s12864-019-6121-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization and evolutionary analysis of heat shock transcription factors (HSFs) to reveal their potential role under abiotic stresses in radish (Raphanus sativus L.)

Abstract: BackgroundAbiotic stresses due to climate change pose a great threat to crop production. Heat shock transcription factors (HSFs) are vital regulators that play key roles in protecting plants against various abiotic stresses. Therefore, the identification and characterization of HSFs is imperative to dissect the mechanism responsible for plant stress responses. Although the HSF gene family has been extensively studied in several plant species, its characterization, evolutionary history and expression patterns i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 84 publications
(110 reference statements)
0
16
0
Order By: Relevance
“…R1 and R4 harbored the most RsCPA genes (Ten, 17.67%), followed by R5 and R6 (Eight, 13.37%), while R3 and R8 contained the least RsCPA genes (Two, 3.33%). Genome duplication events have facilitated the expansion of plant gene families, including whole-genome duplication (WGD)/segmental duplication, dispersed duplication (DD), tandem duplication (TD), proximal duplication (PD), and transposed duplication (TRD) [34][35][36]. The duplication types driving expansion of the RsCPA gene family was explored by Multiple Collinearity Scan toolkit (MCScanX).…”
Section: Chromosomal Localization and Gene Distribution Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…R1 and R4 harbored the most RsCPA genes (Ten, 17.67%), followed by R5 and R6 (Eight, 13.37%), while R3 and R8 contained the least RsCPA genes (Two, 3.33%). Genome duplication events have facilitated the expansion of plant gene families, including whole-genome duplication (WGD)/segmental duplication, dispersed duplication (DD), tandem duplication (TD), proximal duplication (PD), and transposed duplication (TRD) [34][35][36]. The duplication types driving expansion of the RsCPA gene family was explored by Multiple Collinearity Scan toolkit (MCScanX).…”
Section: Chromosomal Localization and Gene Distribution Analysismentioning
confidence: 99%
“…In the process of plant evolution, duplicated genes could obtain new functions or segment existing functions to improve the adaptability of plants [34]. For instance, expansion of the RsHSF gene family was primarily driven by WGD or segmental duplication, which might be largely related with gene duplication [36]. It was previously reported that WGD and PDs event were mainly involved in the expansion of the CPA family in Pyrus bretschneideri [14].…”
Section: Evolutionary Characterization Of the Rscpa Familymentioning
confidence: 99%
“…For example, eight RsHSF genes in radish were highly expressed in leaves, roots, cortex, cambium, and xyloid. The expression pattern of 12 RsHSF genes was also changed under heat, salt, and heavy metals (Tang et al, 2019). Studies revealed the roles of HSFA1 in the osmosis, salt stress, and the oxidative stress response in Arabidopsis (Liu et al, 2011).…”
mentioning
confidence: 99%
“…Comprehensive expression profiling of HSF genes in a number of plant species revealed great variability during development and in response to a number of abiotic and biotic stresses. Diversity in HSF transcription was reported for Arabidopsis (Miller & Mittler, 2006, Swindell, Huebner & Weber, 2007, rice (Chauhan, Khurana, Agarwal & Khurana, 2011, Yang, Wang, Gao, Zhou, Zhang, Hu, Yuan, Liang & Xu, 2014, barley (Reddy, Kavi Kishor, Seiler, Kuhlmann, Eschen-Lippold, Lee, Reddy & Sreenivasulu, 2014), tomato (Fragkostefanakis et al , 2015), wheat (Agarwal & Khurana, 2019, Xue, Sadat, Drenth & McIntyre, 2014, Ye, Yang, Hu, Liu, Li, Zhang & Song, 2020, maize (Yang et al , 2014, Zhang, Li, Fu, Duan, Hu & Guo, 2020a, Brachipodium and sorghum (Nagaraju, Reddy, Kumar, Srivastava, Kishor & Rao, 2015, pepper (Guo, Lu, Zhai, Chai, Gong & Lu, 2015), radish (Tang, Xu, Wang, Cheng, Luo, Xie, Fan & Liu, 2019), physic nut (Zhang, Chen & Shi, 2020b), tea (Xu, Guo, Pang, Zhang, Kong & Liu, 2020), poplar (Liu, Hu & Zhang, 2019a) and chinese cabbage (Huang, Li, Wang, Xu, Huang, Wang, Ma & Xiong, 2015). For example soybean HSF genes were shown to respond diversely to drought or high temperatures.…”
Section: Regulation Of Plant Hsf Genesmentioning
confidence: 99%